Automation Simulation of Plant Watering System using Moisture Sensor Based on Mobile Devices Urban Farming Method - Muhammad Ridwan Effendi; Mohammad Narji (Jurnal Mantik, 2022)
This study makes a set of tools for monitoring soil moisture accompanied by mobile-based plant watering. The benefit of this soil moisture detector accompanied by watering plants is that it can facilitate human work in measuring soil moisture accompanied by watering. The soil moisture monitoring device accompanied by watering plants is composed of electronic components, which consist of Arduino Uno as a system controller of all circuits, a soil moisture sensor to measure soil moisture, how the soil moisture sensor works to measure soil moisture, by plugging a probe. on the ground. While blynk is used to transmit soil moisture signals via mobile phones. The results obtained from reading the sensor values ??are wet, damp and dry according to the predetermined range value. Wet soil conditions with a value range of 150 to 350, moist soil conditions with a range value of 351 to 475, dry soil conditions a value of 476 to 1023. From the results of testing the soil moisture monitoring system and watering plants can detect soil moisture and watering plants, then blynk works automatically to send signals to plant owners via cellphone. The existence of an automatic soil moisture meter and soil watering is expected to facilitate performance in the agricultural sector.